Interpretation of Historic Urban Landscape Genes: A Case Study of Harbin, China - Jianqiao Sun; Long Shao (Land)
The intensifying urbanization has led to the increasing risk of urban landscape character fading away. How to inherit and control the “genes” of urban landscape features is a crucial issue that needs urgent resolution. To address this issue, this study draws on the theory of biological genes, employing methods such as historical information translation, deconstruction and extraction of landscape features, and genetic analysis to establish a research paradigm of “holistic composition interpretation—dynamic evolution interpretation” for historic urban landscape genes. The study applies this paradigm in practice using Harbin, China, as an example. The results indicate that: (1) The historic urban landscape genes are comprised of explicit landscape pattern genes; street and alley texture genes; architectural appearance genes; and implicit human settlement culture genes, industrial culture genes, historical culture genes, and spiritual culture genes. (2) The evolutionary traits of Harbin’s historic urban landscape genes manifest in several ways: the evolution of its landscape pattern genes, featuring “three-tiered terraces, balanced spatial arrangement, surrounded by mountains and rivers, and fan-shaped radial layout”; the evolution of its street and alley texture genes, exhibited through “a blend of Chinese and Western styles, sprawling and interconnected, unit linkage, and multi-dimensional intersections”; the evolution of its architectural style genes, marked by “diverse styles, a harmonious fusion of Chinese and Western elements, grouped interdependence, and adaptation to the times”; the evolution of its human settlement culture genes, highlighted by “a secluded lifestyle, diverse customs, and the coexistence of Chinese and Western cultures”; the evolution of its historical culture genes, distinguished by “unity in diversity and multicultural differentiation”; and the evolution of its spiritual culture genes, characterized by “pluralistic beliefs and inclusiveness”. (3) The essential difference between historic urban landscape genes and other genes lies in their adaptive evolution in response to environmental changes over generations and their ability to reveal the influence mechanisms among genes, between genes and landscape features, and between genes and the environment. The distinction between historic urban landscape genes and other types of genes lies in the adaptive changes that historic urban landscape gene types undergo in response to changes in time and environment. The historic urban landscape gene system itself undergoes adaptive evolution with the urban environment of various historical periods, leading to the emergence and differentiation of new levels. This study can provide new insights into urban heritage conservation, urban landscape management, and rational allocation of urban land use.